Jamovi, the technological tool for analyzing and interpreting data in civil engineering projects - LINO CALLE, VICTOR ALEJANDRO (2024)
Advances in information technology have led to an increased use of statistics as a tool for analyzing data in various academic fields. Statistics has become a primary requirement in any curriculum because of its wide range of applications in the industry and for research purposes. Higher education programs therefore need to prepare graduates with both theoretical and applied statistical knowledge. There are several statistical technology tools for data analysis, each with its own advantages and disadvantages. This article examines Jamovi, a statistical software that is versatile, free and open source, and the impact of this tool on the teaching of statistics for civil engineering. The study involved 40 students of the Masters in Physical Planning of Civil Works of the Universidad Estatal del Sur de Manabí, and was carried out during the months of November to December 2023. The study applied an analytical observational methodology with a quantitative design, using descriptive and inferential statistical techniques. The results showed a better performance of the students who used Jamovi compared to those who used MS Excel. This was supported by descriptive analysis and hypothesis testing. The results led to the conclusion that Jamovi facilitated the teaching and learning process of statistics in civil engineering.